Accounting Principles through the Years: The Views of Professional and Academic Leaders 1938-1954 (Book). - Heath, Loyd C.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Abstract Reviews the book "Accounting Principles Through the Years: The Views of Professional and Academic Leaders 1938-1954," edited by Stephen A. Zeff.